AN ANALYSIS OF INTEGRATED LEARNING MODEL ON STUDENTS’ SPEAKING SKILL IN LEARNING ENGLISH - Nesti Arni Hulu; Adieli Laoli; Elwin Piarawan Zebua; Riswan Zega (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
This research aims to analyze theintegrated learning model to students'speaking skills in English learning for tenthgrader of TKJ at SMK Negeri 1 Alasa. Thisresearch uses a qualitative approach with aphenomenological study method to explorestudents' and teachers' experiences afterapplying the model. Data were obtainedthrough classroom observation and in-depthinterviews with teachers and 20 students. Theresults showed that the integrated learningmodel is suitable as a learning model becausestudents feel that with an integrated learningmodel students easily understand the materialbesides that this learning model is alsointeresting for students. The factors thatinfluence students' speaking skills with the useof this model are able to increase learningmotivation, active involvement of students inthe learning process, and students are able tospeak English properly and correctly. Inaddition, this model also contributes toimproving important aspects of speaking skillssuch as fluency, comprehension, vocabulary,pronunciation and confidence. However, thechallenges faced by teachers in implementingthis model include limited resources, teachingmaterials, technology, and supporting facilitiesand infrastructure in schools. Therefore,support from the school and training forteachers are highly recommended so that theimplementation of integrated learning modelscan run optimally.